Keikutsertaan Bidan Praktik Mandiri terhadap Program Jaminan Kesehatan Nasional - Runjati Runjati; Triana Sri Hardjanti; Sri Rahayu (Jurnal LINK, 2015)
The aim of the research was to analyze the factors that affect participation of Independent Midwives Practice in the National Health Insurance in Semarang City. The research design used analytic observational research. The subjects of the study were 73 IMP and taken by simple random sampling. The data collected using questionnaires. Data were analyzed using Chi Square and multiple logistic regression. The results showed the IMP participation on JKN were 52.1%. There were some relationship between socialization, resources, attitudes and bureaucracy. Attitude and resources had influence with participation on National Health services. IMP who had good attitude had opportunities participate 6 times compare with who did not participate. Resources BPM good opportunity to participate JKN 4.9 times than did not participate.  Midwives need to prepare a good attitude and its resources and cooperation partners being able to support and provide IMP to be able to follow the program of National Health Insurance.